Empowerment of Women-Owned Businesses through Islamic Financial Inclusion Instruments: The Role of Crowdfunding - Al Berto, Muhammad; Hamdun, Nabil Ghazy; Abror, Moh Arifal (Jurnal Ekonomi dan Bisnis Islam (JEBI), 2025)
Women entrepreneurs face financial constraints due to limited access to traditional banking, lack of collateral, and systemic biases. This study explores Sharia-compliant crowdfunding as an alternative financing model to enhance financial inclusion. Using a qualitative approach with library research, the study proposes a model integrating social intermediation (group formation, client appraisal, capacity building) and financial intermediation (qardh hasan for interest-free loans, musyarakah for investment-based financing). Findings suggest this approach can bridge the financing gap, promote women's economic participation, and create a more inclusive financial ecosystem. Expanding Islamic crowdfunding and financial literacy can further empower women entrepreneurs and drive sustainable economic growth.